Wives' participation in household decision-making the case of fishing and non-fishing households of Barangay Parara Norte, Tigbauan, Iloilo - Corpus, Melchor Navat
This is a study on the participation of wives in household decision-making, with an emphasis on the wives from fishing and non-fishing households of Barangay Parara Norte, Municipality of Tigbauan, Province of Iloilo. It aims to: 1)identify the factors that are related to the participation of wives in fishing and non-fishing households in all aspects of household decision-making, 2) identify the areas or aspects of household wives' level of participation in household decision-making and their educational attainment, 3) find out if there is a relationship between wives' level of participation in household decision-making and their educational attainment, 4)find out if there is a relationship between wives' level of participation in household decision-making and their income, and 5)describe the similarities and dissimilarities in the level of participation of wives in decision-making in both fishing and non-fishing households., The study used an interview-schedule that is made up of six parts namely: 1)socio-demographic characteristics of the respondents, 2) financia-economic aspect, 3) socio-moral aspect, 4) political aspect, 5) educational attainment versus participation, and 6) income versus participation. It utilized a Likert type scale where the range of scoring is from 1-3; 1 as disagree, 2 as unsure, and 3 as agree. Books, newspapers, magazines and unpublished works were also utilized to complete the needed data.There were 105 respondents, 36 of whom are from fishing households and 69 are from non-fishing households. It is found that wives in non-fishing households exert great authority in the areas of family budgeting and child rearing, while wives from fishing households exercise great authority in family budgeting, purchase of household appliances, family planning, child rearing, and choice of baptismal, confirmation and wedding of their children. It is also found that, in fishing households, educational attainment plays a significant role in the participation of wives in household decision-making, but not in non-fishing households. Moreover, it is found that income does not affect the participation of wives from two household types. Finally, results show that wives in fishing households have moderately inactive participation in household decision-making while wives from non-fishing households have an average participation in the making of household decisions.